Complimentary Split Ring Resonator (CSRR) As A Viscometer For Engine Oils - Ong, Tze Ching; anak Buja, Andy; Anak George Empam, Alexandria; Yee, See Khee; Sia, Chee Kiong; Ong, Pauline (Teknomekanik, 2021)
A viscometer is a tool used to determine the strength of a fluid to shear or tensile stress. Meanwhile, engine oils are used to reduce friction and wear during operation and often deteriorate by the dynamic process with the combined effects of working conditions, contaminations and wear conditions. Therefore, the precise characterization of viscosity is important in the analysis of numerous engineering situations that consume engine oils that associate the functionality or performance of vehicles and machinery. This work aims to investigate the Complimentary Split Ring Resonator (CSRR) as a viscometer for engine oils. The antenna using radiation path such as CSRR is commonly used to measure the dielectric property of substances. Hence, this approach is applied to identify the dielectric properties of engine oils and establish the correlation between viscosity and dielectric properties. Eight engine oils from Shell were tested based on their margins in the terms of kinematic viscosity. Each oil was tested and repeated three times before the mean values were determined along with the frequency of 1-9GHz. The findings show no convincing and solid correlation between the two variables due to the small dielectric constant variation of engine oil with different viscosity. However, future works using current resonator will be applied in other applications associated with different material properties to build a predictive model. In addition, future work can consider sweeping in low frequency that might show positive results.